(untitled) (International Journal of Physiotherapy, 2025)
Background: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by motor symptoms such as bradykinesia, rigidity, and postural instability, which contribute to delayed reaction times and poor coordination. This study aimed to evaluate the effectiveness of a 2-week Choice Stepping Reaction Time (CSRT) training using the Act-React software in improving reaction time, coordination, and balance in individuals with Parkinson’s disease. Case Summary: A 65-year-old male presented with slowness of movement and balance difficulties diagnosed as idiopathic Parkinson’s with Hoehn & Yahr Stage 2.5, who received intervention including 20-minute CSRT training sessions using Act-React software along with Conventional Physiotherapy over two weeks. Study outcomes were assessed using the Choice Stepping Reaction Time Test (CSRTT), Four-Square Step Test (FSST), Timed Up and Go (TUG) Test, and Balance Error Scoring System (BESS). Outcome Measure: Post-intervention, the patient demonstrated a 55.56% improvement in reaction time (6.3s to 2.84s), an 18% reduction in TUG time (14.8s to 12.1s), a 16% improvement in FSST time (11.4s to 9.6s), and a 25% reduction in BESS errors (12 to 9 errors). Conclusion: CSRT training using Act-React significantly improved reaction time, functional mobility, coordination, and balance in a Parkinson’s disease patient. This intervention shows promise as a rehabilitation tool for addressing motor deficits in PD.